2004
DOI: 10.1167/iovs.03-0777
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Transduced Retinal Pigment Epithelium in Rats

Abstract: RPE cells transduced with neurotrophic factors express the factors after transplantation into the subretinal space. RPE transduced with Axokine or bFGF, in contrast to RPE transduced with BDNF, stimulate an immunologic reaction of the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Still however, there remain major challenges as to the definite feasibility. These include immunological issues, 34 identification of the ideal anatomical niche 35 and ways of application 36 . Further investigation will include a quantitative and qualitative assessment of the integrative capacity of cells into ocular tissue when administered into the ocular cavity as well as a thorough in vivo characterization of their functional properties and their long‐time survival.…”
Section: Discussionmentioning
confidence: 99%
“…Still however, there remain major challenges as to the definite feasibility. These include immunological issues, 34 identification of the ideal anatomical niche 35 and ways of application 36 . Further investigation will include a quantitative and qualitative assessment of the integrative capacity of cells into ocular tissue when administered into the ocular cavity as well as a thorough in vivo characterization of their functional properties and their long‐time survival.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several clinical trials using transplantation of RPE cells have been made to treated age-related macular degeneration 53, 54. Attempts have been made to extend the lifespan of the RPE cells or to transduce these cells with trophic factor before transplantation without success 55, 56. The effect of OTX2 is probably mediated through the maintenance of a proper differentiation status of the grafted cells, which is also relevant in the field of iPSC transplantation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schwartz et al reported that subretinal transplantation of RPE cells derived from human embryonic stem cells resulted in improved visual acuity in a patient with AMD (Schwartz et al 2012). Several studies have shown that transplanted RPE cells transduced with a specific gene remain viable and express the transgene in the subretinal space of the host animal (Osusky et al 1995;Saigo et al 2004). In the present study, we subretinally transplanted Fbln5-overexpressing RPE cells in rats with laserinduced CNV and found that the transplanted RPE cells survived for at least 4 weeks and migrated toward the retina.…”
Section: Discussionmentioning
confidence: 99%